Struktur, Kategori, Dan Fungsi Sosial Pertanyaan Tradisional (Riddles) Masyarakat Nagari Tapi Selo Kecamatan Lintau Buo Utara Kabupaten Tanah Datar - Arif Ramanda Kurnia; Zulfadhli Zulfadhli (Persona: Kajian Bahasa dan Sastra, 2022)
This study aims to (1) describe the traditional question structure (riddles) of the Nagari Tapi Selo community, North Lintau Buo District, Tanah Datar Regency, (2) describe the category of traditional questions (riddles) of the Nagari Tapi Selo community, North Lintau Buo District, Tanah Datar Regency, and ( 3) describe the social function of traditional questions (riddles) of the Nagari Tapi Selo community, North Lintau Buo District, Tanah Datar Regency. This type of research is qualitative with descriptive method. The data for this research are traditional questions (riddles) for the people of Nagari Tapi Selo, North Lintau Buo District, Tanah Datar Regency. Data collection from informants was carried out in two stages, namely recording traditional questions (riddles) and collecting data about the storytelling environment. Data analysis was carried out in four stages (1) the data transcription stage, (2) the data classification stage, (3) the discussion and conclusion stage of the classification or analysis results, and (4) the reporting stage. Based on the results of the study, the following things were found: (1) the traditional question structure (riddles) of the Nagari Tapi Selo community, North Lintau Buo District, Tanah Datar Regency consisted of descriptive and answer elements which were classified into two categories, namely: ( a) conflicting traditional questions (riddles), and (b) non-conflicting traditional questions (riddles). (2) the category of traditional questions (riddles) for the Nagari Tapi Selo community, North Lintau Buo District, Tanah Datar Regency consists of: (a) similarities to humans, (b) similarities to animals, (c) similarities to plants, (d) similarities to objects off, and (e) equality with color. (3) the social functions of traditional questions (riddles) of the Nagari Tapi Selo community, North Lintau Buo District, Tanah Datar Regency were found, namely (a) testing a person's intelligence and (b) as entertainment.